Makna Kekuasaan Ilahi Kajian Tafsir Surat al-Mulk 1 - Dian Erwanto; Nur Ahid (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2022)
Abstract: Everything that has happened on earth and in the universe is evidence of God's power, so among the problems of faith in God is belief in God's power in His power and will that everything depends, God is omniscient, God is omniscient, God is omnipotent, has absolute power. perfect, this has been stated in the Qur'an in which it explains the greatness of Allah's creation, both theoretically, cause and effect. This study highlights aspects of the meaning of the Koran in the interpretation of Surat al-Mulk about the kingdom of God, the nature of God's power, this research was conducted using a descriptive-analysis-based literature study of the text in the form of verses of the Koran, so that the book itself is used as a source of information. primary. The research results obtained are as follows: First; The format of the interpretation of al-Mulk's letter, both in the dzohir text and behind the meaning, in this interpretation leads to the I'tiqadi interpretation style. Second; Operationalization and logical reasoning on the implications of understanding the nature of God's power and kingdom